The impact of the COVID-19 pandemic on international students’ perception of service quality (Case study of the University of Split) - Ivana Jadrić; Đurđica Miletić; Ana Ćosić (Ekonomski Vjesnik, 2022)
Purpose: Development opportunities of higher education institutions (HEI) arising from international activities are constantly evolving, increasing at the same time their complexity. Consequently, numerous activities have been created to connect different higher education institutions across Europe, where the biggest challenge of internationalisation today is the European Universities Initiative. In that context, it is important to measure whether the European Union initiative created better resilience to the COVID-19 pandemic.